Using Drone‐Derived Imagery to Describe Prey Sharing Behaviors in Two Piscivorous Resident Killer Whale Populations - Sharon W. C. Kay; Lance G. Barrett‐Lennard; Brittany C. Visona‐Kelly; Marie‐Ana Mikus; Michael N. Weiss; Darren P. Croft; Valeria Vergara; Holly Fearnbach; John W. Durban; Chris T. Darimont (Marine Mammal Science, 2026)
Cooperative foraging occurs across diverse taxa and facilitates prey acquisition and social learning, particularly when prey is shared among group members. In Resident killer whales ( Orcinus orca ater ), prey sharing is central to how individuals acquire salmonid prey, yet current research has relied primarily on boat‐based observations. Using 10 years of drone‐based imagery, we examined prey sharing behaviors in two populations, endangered Southern Resident killer whales (SRKWs) and threatened Northern Resident killer whales (NRKWs). Our goal was to evaluate the utility of drones for documenting prey sharing behaviors and conduct preliminary comparisons between NRKW and SRKWs. We detected 41 NRKW and 52 SRKW predation events, with prey sharing observed in 24 NRKW (59%) and 22 SRKW (42%) events. Drones effectively documented prey sharing at or near the surface, revealing subtle behaviors and allowing us to track the roles of individuals. Initial comparisons revealed that adult female NRKWs shared prey more frequently than adult female SRKWs and shared larger portions of prey. Although preliminary, our findings suggest differences in prey sharing between the populations, possibly reflecting social or ecological differences. Overall, drone‐based methods provide valuable insights into foraging behavior in free‐ranging cetaceans and offer a new approach to investigate cooperative behaviors.

Rolling in the deep: drivers of social preferences and social interactions within a bull shark aggregation in Fiji - Natasha D. Marosi; Samuel Ellis; David M.P. Jacoby; Juerg M. Brunnschweiler; Darren P. Croft (Animal Behaviour, 2026)

Comparison of black carbon media for removal of dissolved metals in stormwater - Kristen Croft; Sabrina De Nicola; Chen Yuan; Devrim Kaya; Allen P. Davis; Birthe V. Kjellerup (Journal of Contaminant Hydrology, 2026)

Global retrieval of canopy chlorophyll content from Sentinel-3 OLCI TOA data using a two-step upscaling method integrating physical and machine learning models - Dong Li; Holly Croft; Gregory Duveiller; Adam P. Schreiner-McGraw; Anirudh Belwalkar; Tao Cheng; Yan Zhu; Weixing Cao; Kang Yu (Remote Sensing of Environment, 2025)

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Treatment of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) in stormwater using polishing columns with biochar and granular activated carbon - Chen Yuan; Kristen Croft; Sabrina de Nicola; Allen P. Davis; Birthe V. Kjellerup (Chemosphere, 2025)

Source specific fine particles and rates of asthma and COPD healthcare encounters pre- and post-implementation of the Tier 3 vehicle emissions control regulations - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; Philip K. Hopke; David Q. Rich (Journal of Hazardous Materials, 2025)

PM2.5 and its components and respiratory disease healthcare encounters – Unanticipated increased exposure-response relationships in recent years after environmental policies - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Philip K. Hopke; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; David Q. Rich (Environmental Pollution, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The effect of formation swimming on tailbeat and breathing frequencies in killer whales - Federica Spina; Michael N. Weiss; Darren P. Croft; Paolo Luschi; Alessandro Massolo; Paolo Domenici (Behavioral Ecology and Sociobiology, 2024)
In many aquatic taxa, formation traveling can reduce the energetic expenditure of locomotion by exploiting the vorticity trails shed by neighbors or through drafting. Cetaceans, especially odontocetes, often swim in groups; nevertheless, the possibility that whales gain energetic benefits from swimming in formation remains poorly studied, apart from mother-calf pairs. Between June and September in 2019 and 2021, we recorded aerial videos of Southern Resident killer whales ( Orcinus orca ) in the Salish Sea (USA) travelling in groups. We estimated whale tailbeat and breathing frequencies as proxies of the relative energetic costs of swimming, and tested the effect of swimming speed, relative positioning (e.g., leaders, whales in the middle of groups, or followers), sex and estimated size on these observed proxies. Our results reveal a complex relationship between physical characteristics, relative positioning, and energetic proxies. Intervals between respiration lasted longer in large-sized trailing individuals, but the overall breathing frequency was similar for all whales regardless of their position. The tailbeat frequency was mainly associated to whale sex, size, and swimming speed; in addition, tailbeat frequency showed a decreasing trend as the number of individuals in the formation increased. We found moderate evidence that position-based energetic effects may be present in the formation swimming of killer whales, and it is likely that additional factors such as social ties and hierarchies, play a key role in determining individual positioning in travelling groups. Significance Swimming in formation has been extensively studied in fish and other aquatic animals and has been documented to provide energetic advantages. Our understanding of the potential energetic benefits of wild cetacean formation swimming has been constrained by the difficulties of studying the movement of whale groups from traditional observation platforms. In recent years, non-invasive observations of cetaceans using unoccupied aerial systems have significantly improved the observation of these species in the wild, providing an exciting opportunity to better understand their behaviors and habits. Our results show a tendency for formation swimming to affect two energetic proxies (tailbeat frequency and the duration of underwater intervals between surfacing events). The results of this study set the stage for further research to identify the multiple determinants affecting killer whale formation swimming which go beyond purely energetic advantages, e.g. social relationships.

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Interactions of particulate- and dissolved-phase heavy metals in a mature stormwater bioretention cell - Kristen Croft; Birthe V. Kjellerup; Allen P. Davis (Journal of Environmental Management, 2024)

Nitrate: The Dr. Jekyll and Mr. Hyde of human health? - Catherine P. Bondonno; Liezhou Zhong; Nicola P. Bondonno; Marc Sim; Lauren C. Blekkenhorst; Alex Liu; Anjana Rajendra; Pratik Pokharel; Dorit W. Erichsen; Oliver Neubauer; Kevin D. Croft; Jonathan M. Hodgson (Trends in Food Science & Technology, 2023)

High frequency UV–Vis sensors estimate error in riverine dissolved organic carbon load estimates from grab sampling - J. P. Ritson; O. Kennedy-Blundell; J. Croft; M. R. Templeton; C. E. Hawkins; J. M. Clark; M. G. Evans; R. E. Brazier; D. Smith; N. J. D. Graham (Environmental Monitoring and Assessment, 2022)
High frequency ultraviolet – visible (UV–VIS) sensors offer a way of improving dissolved organic carbon (DOC) load estimates in rivers as they can be calibrated to DOC concentration. This is an improvement on periodic grab sampling, or the use of pumped sampling systems which store samples in-field before collection. We hypothesised that the move to high frequency measurements would increase the load estimate based on grab sampling due to systemic under-sampling of high flows. To test our hypotheses, we calibrated two sensors in contrasting catchments (Exe and Bow Brook, UK) against weekly grab sampled DOC measurements and then created an hourly time series of DOC for the two sites. Taking this measurement as a ‘true’ value of DOC load, we simulated 1,000 grab sampling campaigns at weekly, fortnightly and monthly frequency to understand the likely distribution of load and error estimates. We also performed an analysis of daily grab samples collected using a pumped storage sampling system with weekly collection. Our results show that: a) grab sampling systemically underestimates DOC loads and gives positively skewed distributions of results, b) this under-estimation and positive skew decreases with increasing sampling frequency, c) commonly used estimates of error in the load value are also systemically lowered by the oversampling of low, stable flows due to their dependence on the variance in the flow-weighted mean concentration, and d) that pumped storage systems may lead to under-estimation of DOC and over estimation of specific ultra-violet absorbance (SUVA), a proxy for aromaticity, due to biodegradation during storage.

Partial sex linkage and linkage disequilibrium on the guppy sex chromosome - Suo Qiu; Lengxob Yong; Alastair Wilson; Darren P. Croft; Chay Graham; Deborah Charlesworth (Molecular Ecology, 2022)
The guppy Y chromosome has been considered a model system for the evolution of suppressed recombination between sex chromosomes, and it has been proposed that complete sex‐linkage has evolved across about 3 Mb surrounding this fish's sex‐determining locus, followed by recombination suppression across a further 7 Mb of the 23 Mb XY pair, forming younger “evolutionary strata”. Sequences of the guppy genome show that Y is very similar to the X chromosome. Knowing which parts of the Y are completely nonrecombining, and whether there is indeed a large completely nonrecombining region, are important for understanding its evolution. Here, we describe analyses of PoolSeq data in samples from within multiple natural populations from Trinidad, yielding new results that support previous evidence for occasional recombination between the guppy Y and X. We detected recent demographic changes, notably that downstream populations have higher synonymous site diversity than upstream ones and other expected signals of bottlenecks. We detected evidence of associations between sequence variants and the sex‐determining locus, rather than divergence under a complete lack of recombination. Although recombination is infrequent, it is frequent enough that associations with SNPs can suggest the region in which the sex‐determining locus must be located. Diversity is elevated across a physically large region of the sex chromosome, conforming to predictions for a genome region with infrequent recombination that carries one or more sexually antagonistic polymorphisms. However, no consistently male‐specific variants were found, supporting the suggestion that any completely sex‐linked region may be very small.

The effect of age, sex, and resource abundance on patterns of rake markings in resident killer whales ( Orcinus orca ) - Charli Grimes; Lauren J. N. Brent; Michael N. Weiss; Daniel W. Franks; Kenneth C. Balcomb; David K. Ellifrit; Samuel Ellis; Darren P. Croft (Marine Mammal Science, 2022)
Fluctuations in aggressive behavior of group‐living species can reflect social conflict and competition for resources faced by individuals throughout their lifespan and can negatively impact survival and reproduction. In marine mammals, where social interactions are difficult to observe, tooth rake marks can be used as an indicator of received aggression. Using 38 years of photographic data, we quantified the occurrence of tooth rake marks on wild resident killer whales ( Orcinus orca ), examining the effects of age, sex, and prey abundance on rake density. Our analysis revealed sex and age effects, with males exhibiting higher rake density than females and rake density declining significantly with age. Contrary to predictions, we observed an increase in rake density across the population as the abundance of their primary food resource, Chinook salmon ( Oncorhynchus tshawytscha ), increased. These results provide indirect evidence of fluctuations in received aggression from conspecifics across the lifespan of an individual, possibly reflecting changes in patterns of social conflict which may be mediated by resource abundance. Our findings highlight the need for further research to examine the fitness consequences of aggression in killer whales and to understand the proximate mechanisms by which resource abundance influences rates of aggression in the population.

Sensory‐based quantification of male colour patterns in Trinidadian guppies reveals no support for parallel phenotypic evolution in multivariate trait space - Lengxob Yong; Darren P. Croft; Jolyon Troscianko; Indar W. Ramnarine; Alastair J. Wilson (Molecular Ecology, 2022)
Parallel evolution, in which independent populations evolve along similar phenotypic trajectories, offers insights into the repeatability of adaptive evolution. Here, we revisit a classic example of parallelism, that of repeated evolution of brighter males in the Trinidadian guppy ( Poecilia reticulata ). In guppies, colonisation of low predation habitats is associated with emergence of ‘more colourful’ phenotypes since predator‐induced viability selection for crypsis weakens while sexual selection by female preference for conspicuousness remains strong. Our study differs from previous investigations in three respects. First, we adopted a multivariate phenotyping approach to characterise parallelism in multitrait space. Second, we used ecologically‐relevant colour traits defined by the visual systems of the two selective agents (i.e., guppy, predatory cichlid). Third, we estimated population genetic structure to test for adaptive (parallel) evolution against a model of neutral phenotypic divergence. We find strong phenotypic differentiation that is inconsistent with a neutral model but very limited support for the predicted pattern of greater conspicuousness at low predation. Effects of predation regime on each trait were in the expected direction, but weak, largely nonsignificant, and explained little among‐population variation. In multitrait space, phenotypic trajectories of lineages colonising low from high predation regimes were not parallel. Our results are consistent with reduced predation risk facilitating adaptive differentiation, potentially by female choice, but suggest that this proceeds in independent directions of multitrait space across lineages. Pool‐sequencing data also revealed SNPs showing greater differentiation than expected under neutrality, among which some are found in genes contributing to colour pattern variation, presenting opportunities for future genetic study.

Editorial: Sociality in the Marine Environment - David M. P. Jacoby; Culum Brown; Darren P. Croft; Janet Mann; Johann Mourier (Frontiers in Marine Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Diversity and Consequences of Social Network Structure in Toothed Whales - Michael N. Weiss; Samuel Ellis; Darren P. Croft (Frontiers in Marine Science, 2021)
Toothed whales (suborder Odontoceti) are highly social, large brained mammals with diverse social systems. In recent decades, a large body of work has begun investigating these dynamic, complex societies using a common set of analytical tools: social network analysis. The application of social network theory to toothed whales enables insight into the factors that underlie variation in social structure in this taxon, and the consequences of these structures for survival, reproduction, disease transmission, and culture. Here, we perform a systematic review of the literature regarding toothed whale social networks to identify broad patterns of social network structure across species, common drivers of individual social position, and the consequences of network structure for individuals and populations. We also identify key knowledge gaps and areas ripe for future research. We recommend that future studies attempt to expand the taxonomic breadth and focus on standardizing methods and reporting as much as possible to allow for comparative analyses to test evolutionary hypotheses. Furthermore, social networks analysis may provide key insights into population dynamics as indicators of population health, predictors of disease risk, and as direct drivers of survival and reproduction.

Mixture models as a method for comparative sociality: social networks and demographic change in resident killer whales - Samuel Ellis; Daniel W. Franks; Michael N. Weiss; Michael A. Cant; Paolo Domenici; Kenneth C. Balcomb; David K. Ellifrit; Darren P. Croft (Behavioral Ecology and Sociobiology, 2021)
In studies of social behaviour, social bonds are usually inferred from rates of interaction or association. This approach has revealed many important insights into the proximate formation and ultimate function of animal social structures. However, it remains challenging to compare social structure between systems or time-points because extrinsic factors, such as sampling methodology, can also influence the observed rate of association. As a consequence of these methodological challenges, it is difficult to analyse how patterns of social association change with demographic processes, such as the death of key social partners. Here we develop and illustrate the use of binomial mixture models to quantitatively compare patterns of social association between networks. We then use this method to investigate how patterns of social preferences in killer whales respond to demographic change. Resident killer whales are bisexually philopatric, and both sexes stay in close association with their mother in adulthood. We show that mothers and daughters show reduced social association after the birth of the daughter’s first offspring, but not after the birth of an offspring to the mother. We also show that whales whose mother is dead associate more with their opposite sex siblings and with their grandmother than whales whose mother is alive. Our work demonstrates the utility of using mixture models to compare social preferences between networks and between species. We also highlight other potential uses of this method such as to identify strong social bonds in animal populations. Significance statement Comparing patters of social associations between systems, or between the same systems at different times, is challenging due to the confounding effects of sampling and methodological differences. Here we present a method to allow social associations to be robustly classified and then compared between networks using binomial mixture models. We illustrate this method by showing how killer whales change their patterns of social association in response to the birth of calves and the death of their mother. We show that after the birth of her calf, females associate less with their mother. We also show that whales’ whose mother is dead associate more with their opposite sex siblings and grandmothers than whales’ whose mother is alive. This clearly demonstrates how this method can be used to examine fine scale temporal processes in animal social systems.

Intraspecific variation in inhibitory motor control in guppies, Poecilia reticulata - Alessandro Macario; Safi K. Darden; Frederick Verbruggen; Darren P. Croft (Journal of Fish Biology, 2021)
Inhibitory control (IC) is the ability to overcome impulsive or prepotent but ineffective responses in favour of more appropriate behaviours. The ability to inhibit internal predispositions or external temptations is vital in coping with a complex and variable world. Traditionally viewed as cognitively demanding and a main component of executive functioning and self‐control, IC was historically examined in only a few species of birds and mammals but recently a number of studies has shown that a much wider range of taxa rely on IC. Furthermore, there is growing evidence that inhibitory abilities may vary within species at the population and individual levels owing to genetic and environmental factors. Here we use a detour‐reaching task, a standard paradigm to measure motor inhibition in nonhuman animals, to quantify patterns of interindividual variation in IC in wild‐descendant female guppies, Poecilia reticulata . We found that female guppies displayed inhibitory performances that were, on average, half as successful as the performances reported previously for other strains of guppies tested in similar experimental conditions. Moreover, we showed consistent individual variation in the ability to inhibit inappropriate behaviours. Our results contribute to the understanding of the evolution of fish cognition and suggest that IC may show considerable variation among populations within a species. Such variation in IC abilities might contribute to individual differences in other cognitive functions such as spatial learning, quantity discrimination or reversal learning.

Changes and consistencies in marine and coastal bird numbers on Kidney Island (Falkland Islands) over half a century - P. Catry; T. J. Clark; S. Crofts; A. Stanworth; E. D. Wakefield (Polar Biology, 2019)

Measuring the complexity of social associations using mixture models - Michael N. Weiss; Daniel W. Franks; Darren P. Croft; Hal Whitehead (Behavioral Ecology and Sociobiology, 2019)

Daily land use regression estimated woodsmoke and traffic pollution concentrations and the triggering of ST-elevation myocardial infarction: a case-crossover study - David Q. Rich; Mark J. Utell; Daniel P. Croft; Sally W. Thurston; Kelly Thevenet-Morrison; Kristin A. Evans; Frederick S. Ling; Yilin Tian; Philip K. Hopke (Air Quality, Atmosphere & Health, 2018)

Contact networks structured by sex underpin sex‐specific epidemiology of infection - Matthew J. Silk; Nicola L. Weber; Lucy C. Steward; David J. Hodgson; Mike Boots; Darren P. Croft; Richard J. Delahay; Robbie A. McDonald (Ecology Letters, 2018)
Contact networks are fundamental to the transmission of infection and host sex often affects the acquisition and progression of infection. However, the epidemiological impacts of sex‐related variation in animal contact networks have rarely been investigated. We test the hypothesis that sex‐biases in infection are related to variation in multilayer contact networks structured by sex in a population of European badgers Meles meles naturally infected with Mycobacterium bovis . Our key results are that male‐male and between‐sex networks are structured at broader spatial scales than female‐female networks and that in male‐male and between‐sex contact networks, but not female‐female networks, there is a significant relationship between infection and contacts with individuals in other groups. These sex differences in social behaviour may underpin male‐biased acquisition of infection and may result in males being responsible for more between‐group transmission. This highlights the importance of sex‐related variation in host behaviour when managing animal diseases.

Stress and welfare in ornamental fishes: what can be learned from aquaculture? - C. H. Stevens; D. P. Croft; G. C. Paull; C. R. Tyler (Journal of Fish Biology, 2017)
The ornamental fish trade is estimated to handle up to 1·5 billion fishes. Transportation and handling of fishes imposes a range of stressors that can result in mortality at rates of up to 73%. These rates vary hugely, however, and can be as low as 2%, because they are generally estimated rather than based on experimental work. Given the numbers of ornamental fishes traded, any of the estimated mortality rates potentially incur significant financial losses and serious welfare issues. Industry bodies, such as the Ornamental Aquatic Trade Association (OATA), have established standards and codes of best practice for handling fishes, but little scientific research has been conducted to understand the links between stress, health and welfare in ornamental species. In aquaculture, many of the same stressors occur as those in the ornamental trade, including poor water quality, handling, transportation, confinement, poor social and physical environment and disease and in this sector directed research and some resulting interventions have resulted in improved welfare standards. This review considers the concept of welfare in fishes and evaluates reported rates of mortality in the ornamental trade. It assesses how the stress response can be quantified and used as a welfare indicator in fishes. It then analyses whether lessons from aquaculture can be usefully applied to the ornamental fish industry to improve welfare. Finally, this analysis is used to suggest how future research might be directed to help improve welfare in the ornamental trade.

Dietary Nitrate, Nitric Oxide, and Cardiovascular Health - Catherine P. Bondonno; Kevin D. Croft; Jonathan M. Hodgson (Critical Reviews in Food Science and Nutrition, 2016)

Assessment of resistance to root-lesion and root-knot nematodes in Australian hybrid clones of sugarcane and its wild relatives - S. A. Bhuiyan; B. J. Croft; G. R. Stirling; E. Wong; P. Jackson; M. Cox (Australasian Plant Pathology, 2016)

Shark personalities? Repeatability of social network traits in a widely distributed predatory fish - David M. P. Jacoby; Lauren N. Fear; David W. Sims; Darren P. Croft (Behavioral Ecology and Sociobiology, 2014)

Social networks in elasmobranchs and teleost fishes - A D M Wilson; D P Croft; J Krause (Fish and Fisheries, 2014)
Over the last decade, there has been an exponential increase in studies using social network analysis to describe the structure of animal societies. In this synthesis, we examine the contribution of social network analysis towards developing our understanding of the social organization of elasmobranchs and teleost fishes. We review and discuss the current state of knowledge of the mechanisms and functions underpinning social network structure in fishes with particular emphasis on cooperation, familiarity, site fidelity, population structure and the welfare of captive populations. We also discuss important methodological issues (e.g. how to identify and mark fish) and highlight new developments in this area of research and their implications for the study of fish behaviour. Finally, we outline promising future research areas for the application of social network analysis to teleost fishes and elasmobranchs.

Dynamic social networks in guppies (Poecilia reticulata) - Alexander D. M. Wilson; Stefan Krause; Richard James; Darren P. Croft; Indar W. Ramnarine; Karoline K. Borner; Romain J. G. Clement; Jens Krause (Behavioral Ecology and Sociobiology, 2014)

Spatial proximity loggers for recording animal social networks: consequences of inter-logger variation in performance - N. K. Boyland; R. James; D. T. Mlynski; J. R. Madden; D. P. Croft (Behavioral Ecology and Sociobiology, 2013)

Increasing trend in the number of Southern Rockhopper Penguins (Eudyptes c. chrysocome) breeding at the Falkland Islands - A. M. M. Baylis; A. C. Wolfaardt; S. Crofts; P. A. Pistorius; N. Ratcliffe (Polar Biology, 2013)

The role of relatedness in structuring the social network of a wild guppy population - Darren P. Croft; P. B. Hamilton; S. K. Darden; D. M. P. Jacoby; R. James; E. M. Bettaney; C. R. Tyler (Oecologia, 2012)

Social behaviour in sharks and rays: analysis, patterns and implications for conservation - David M P Jacoby; Darren P Croft; David W Sims (Fish and Fisheries, 2012)
There are widespread records of grouping behaviour in both adult and juvenile sharks and rays (Class Chondrichthyes, Subclass Elasmobranchii). Yet despite burgeoning descriptions of these events, many of the proximate and ultimate causes of group living in these top predators remain elusive. Given the documented negative anthropogenic effects on many shark populations globally, there is an increasing need to understand how behaviourally mediated grouping influences population distributions and abundance, and the role this plays in exacerbating vulnerability to fishing mortality. Here, we analyse group living in elasmobranchs: we describe our current understanding of the patterns, mechanisms and functions of both aggregation (where grouping is not driven by social mechanisms) and social grouping (where grouping is influenced by social interaction) and discuss some of the current methods used to study social behaviour in this taxa. In particular, social preferences in elasmobranchs have received relatively little attention. We propose that the study of shark aggregations may benefit from a more fine‐scale analytical approach offered by detailed exploration of social interactions using social network analysis. Better understanding of the frequency and longevity of social relations, in conjunction with current long‐term data on habitat use and site philopatry, will likely serve for a more informed approach to coastal and pelagic elasmobranch conservation initiatives.

The effect of familiarity on aggregation and social behaviour in juvenile small spotted catsharks Scyliorhinus canicula - D. M. P. Jacoby; D. W. Sims; D. P. Croft (Journal of Fish Biology, 2012)
This study was designed to address whether juvenile small spotted catsharks Scyliorhinus canicula aggregate and to determine whether potential aggregation is underpinned by social preferences for conspecifics. Using controlled and replicated experiments, the role of familiarity as a potential mechanism driving aggregation and social behaviour in this species was considered. Observed S. canicula association data compared to null model simulations of random distributions revealed differences in aggregation under different social contexts. Only familiar juvenile S. canicula aggregated more than would be expected from random distribution across their habitat. Familiarity increased the mean number of groups but did not significantly affect mean group size. Significant preference and avoidance behaviour across all groups were also observed. Furthermore, the strength of social attraction, quantified by the mean association index, was significantly higher in groups containing familiar individuals. Mixed familiar and unfamiliar treatments were also conducted to test for within‐ and between‐group effects, finding high variation across replicates with some groups assorting by familiarity and others not. It is believed that this study is the first to examine experimentally the influence of conspecific familiarity on aggregation behaviour in sharks. These results not only imply a functional benefit to aggregation, but also suggest that persistent social affiliation is likely to influence dispersal following hatching in this small benthic elasmobranch.

Kin and familiarity influence association preferences and aggression in the mangrove killifish Kryptolebias marmoratus - M. Edenbrow; D. P. Croft (Journal of Fish Biology, 2012)
Association preferences and aggression intensity were investigated in relation to kin and familiarity in the self‐fertilizing, clonal vertebrate, the mangrove killifish Kryptolebias marmoratus . Results indicated that fish preferentially associated with and exhibited less intense aggression towards members of their own genotype (kin), compared to members of a different genotype (non‐kin). Furthermore, when fish were presented with stimulus groups of the same genotype that were familiar or unfamiliar, fish preferentially associated with and exhibited lower aggression intensity directed towards familiar groups. These results indicate that this species prefer to associate with both kin and familiar individuals and modulate aggression accordingly. These results are discussed with reference to the adaptive benefits of kin recognition and preferences for familiars, and place results within the context of current knowledge of the ecology of K. marmoratus .

Effect of gyrodactylid ectoparasites on host behaviour and social network structure in guppies Poecilia reticulata - Darren P. Croft; Mathew Edenbrow; Safi K. Darden; Indar W. Ramnarine; Cock van Oosterhout; Joanne Cable (Behavioral Ecology and Sociobiology, 2011)

Isolation and identification of cytoskeleton-associated prolamine mRNA binding proteins from developing rice seeds - Andrew J. Crofts; Naoko Crofts; Julian P. Whitelegge; Thomas W. Okita (Planta, 2010)

Behavioural trait assortment in a social network: patterns and implications - Darren P. Croft; Jens Krause; Safi K. Darden; Indar W. Ramnarine; Jolyon J. Faria; Richard James (Behavioral Ecology and Sociobiology, 2009)

Potential banana skins in animal social network analysis - Richard James; Darren P. Croft; Jens Krause (Behavioral Ecology and Sociobiology, 2009)

RISK‐SENSITIVE ANTIPREDATOR BEHAVIOR IN THE TRINIDADIAN GUPPY, POECILIA RETICULATA - M. S. Botham; R. K. Hayward; L. J. Morrell; D. P. Croft; J. R. Ward; I. Ramnarine; J. Krause (Ecology, 2008)
The comparative approach has become a powerful tool for understanding how predation has shaped prey behavior. In this study we recorded the occurrence of common aquatic predator species and their densities in seven natural populations of Trinidadian guppies, Poecilia reticulata . We then exposed shoals of guppies from each of these populations to a series of predator treatments. Predator treatments differed in the species of predator used (pike cichlids, Crenicichla frenata ; rivulus, Rivulus hartii ; and freshwater prawns, Macrobrachium carcinus ) and thus in the level of risk posed. We recorded the antipredator responses of guppies in each of these predator treatments. The strength of antipredator behavior shown by guppies was affected by both the type of predator they were exposed to and the level of predation risk they experienced naturally in the wild. Importantly, we found that guppies from high‐risk populations showed a heightened response, compared to those from lower risk populations, only when exposed to the predator species that posed the greatest risk. Our results show the importance of individual predator species in shaping the behavioral traits of prey species at the population level. This has implications for prey movement between habitats that are geographically close but differ greatly in predator fauna.

Sugarcane smut in Queensland: arrival and emergency response - B. J. Croft; R. C. Magarey; P. G. Allsopp; M. C. Cox; T. G. Willcox; B. J. Milford; E. S. Wallis (Australasian Plant Pathology, 2008)

Social network theory in the behavioural sciences: potential applications - J. Krause; D. P. Croft; R. James (Behavioral Ecology and Sociobiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Numerical simulation of sea and bay breezes in a weak shear environment - D. Lu; L. White; R. S. Reddy; P. J. Croft; J. M. Medlin (Meteorology and Atmospheric Physics, 2006)

Social structure and co-operative interactions in a wild population of guppies (Poecilia reticulata) - D. P. Croft; R. James; P. O. R. Thomas; C. Hathaway; D. Mawdsley; K. N. Laland; J. Krause (Behavioral Ecology and Sociobiology, 2006)

Is the distribution of Fiji leaf gall in Australian sugarcane explained by variation in the vector Perkinsiella saccharicida ? - A. W. Ridley; K. Dhileepan; K. N. Johnson; P. G. Allsopp; K. A. Nutt; G. H. Walter; B. J. Croft (Australasian Plant Pathology, 2006)

Social defeat increases alcohol preference of C57BL/10 strain mice; effect prevented by a CCKB antagonist - A. P. Croft; S. P. Brooks; J. Cole; H. J. Little (Psychopharmacology, 2005)

The effects of dexamphetamine on simulated driving performance - B. Y. Silber; K. Papafotiou; R. J. Croft; E. Ogden; P. Swann; C. Stough (Psychopharmacology, 2005)

Assortative interactions and social networks in fish - D. P. Croft; R. James; A. J. W. Ward; M. S. Botham; D. Mawdsley; J. Krause (Oecologia, 2005)

Intra‐sexual preferences for familiar fish in male guppies - D. P. Croft; B. J. Arrowsmith; M. Webster; J. Krause (Journal of Fish Biology, 2004)
Male guppies Poecilia reticulata were observed to develop shoaling preferences for familiar males over a 12 day period, at which time they showed a clear preference for familiar over non‐familiar males.

Sex-biased movement in the guppy ( Poecilia reticulata ) - Darren P. Croft; Brett Albanese; Bethany J. Arrowsmith; Marc Botham; Michael Webster; Jens Krause (Oecologia, 2003)

When fish shoals meet: outcomes for evolution and fisheries - Darren P Croft; Jens Krause; Iain D Couzin; Tony J Pitcher (Fish and Fisheries, 2003)
The mechanisms underlying the social structure of free‐ranging fish shoals have received little attention in comparison to functional studies on shoaling. Recently, however, a number of investigations, both in the marine and in the freshwater environment, have begun to address the underlying mechanisms by concentrating on interactions between free‐ranging shoals. The rates of shoal encounters can influence the opportunities for individual assortment by phenotype and selection of shoal size; act as a constraint on the observed patterns of shoal structure by restricting individual choice behaviour and were found to be high in several small freshwater species (where intershoal distances were small), but lower in marine species where shoals were more dispersed. The duration of encounters may play a role in that it affects both the time available for assessment (of the encountered shoal) as well as that for exchange of individuals. Scarce published information on the outcome of shoal encounters suggests that the outcome of shoal encounters is influenced by shoal composition but not by shoal size. Individual behaviour may have evolved to maintain shoal size when shoals encounter, but when fish populations are depleted by fishing, this trait can exacerbate range and stock collapse. Furthermore, an understanding of the dynamics of shoal encounters has important consequences for the evolution of reciprocal altruism and the transmission of information through social learning within populations. Finally, information on encounter rates between shoals and the number of individuals that are exchanged on such occasions could be important for making predictions about the spread of disease through fish populations.

Development of PCR-based markers for detection of Leifsonia xyli subsp. xyli in fibrovascular fluid of infected sugarcane plants - P. W. J. Taylor; L. A. Petrasovits; R. Van der Velde; R. G. Birch; B. J. Croft; M. Fegan; G. R. Smith; S. M. Brumbley (Australasian Plant Pathology, 2003)

Game management in early prehistoric Cyprus - P. W. Croft (European Journal of Wildlife Research, 2002)

Seasonal aggregations of Canadian east coast pollock as inferred from the commercial fishery and hydroacoustic observations - J. D. Neilson; L. Annis; P. Perley; A. Clay; C. Croft; M. O'Connor (Journal of Fish Biology, 2002)
Data from an otter trawler fleet fishing on the Scotian Shelf combined with year‐round hydroacoustic data indicated that the locations of aggregations of pollock Pollachius virens did not change appreciably from month to month. The proportion of pollock mass compared with total catch mass in individual trawl catches, however, tended to be higher from September to February. The period of highest catch rates was shown to be the December to January period. This period coincided with the period when pollock had the least affinity with the seabed based on information from hydroacoustic observations, a behavioural consideration for acoustic survey design. Based on these observations, it was concluded that the optimal time to conduct an acoustic survey was during the December to January period.

A grid‐net technique for the analysis of fish positions within free‐ranging shoals - D. J. Hoare; A. J. W. Ward; I. D. Couzin; D. P. Croft; J. Krause (Journal of Fish Biology, 2001)
The design and operation of a grid‐net are described, which allows the capture of entire shoals of wild fish and preserves information about the two‐dimensional structure of shoals and the spatial positions of individual fish within the shoal. This simple technique facilitates investigation of several aspects of individual differences in fish shoaling behaviour in the wild for the first time.

Cunxi Wang · Kevan P.C. Croft · David F. Hildebrand - C. Wang; K. P. C. Croft; D. F. Hildebrand (Plant Cell Reports, 2001)

Larval size relative to larval feeding, cannibalism of larvae, egg or adult female size and larval–adult setal patterns among 13 phytoseiid mite species - B.A. Croft; H.-K. Luh; P. Schausberger (Experimental and Applied Acarology, 1999)

Prey-food types of Neoseiulus fallacis (Acari:Phytoseiidae) and literature versus experimentally derived prey-food estimates for five phytoseiid species - P.D. Pratt; P. Schausberger; B.A. Croft (Experimental and Applied Acarology, 1999)

Larval morphology and development of the parasitoidDacnusa sibirica [Hym.: Braconidae] in the leafminer hostChromatomyia syngenesiae - P. Croft; M. J. W. Copland (BioControl, 1994)